PENGARUH PROSES PEMBELAJARAN PRAKARYA DAN KEWIRAUSAHAAN SERTA SARANA DAN PRASARANA PENDIDIKAN TERHADAP SIKAP BERWIRAUSAHA SISWA KELAS XI IIS SMA NEGERI 4 SURAKARTA TAHUN AJARAN 2016/2017 - Betty Uswatun Khasanah; Trisno Martono; Budi Wahyono (Department of Economics Education, Universitas Sebelas Maret, 2017)
This research was a quantitative research using a descriptive method with correlation study. The population in this research are all students of XI IIS’s class at SMA Negeri 4 Surakarta in academic year of 2016/2017. All member of population in this research used as sample research, so this research was a populastion research. Try out of research instrument was conducted on 30 respondents out of sample, students of XI MIA’s class at SMA Negeri 4 Surakarta in academic year of 2016/2017. Data were obtained by using observation, interview, questionnaire, and document analysis. Data were analyzed by using multiple linear regression analysis technique with level significance 0.05. Based on results of this research can be concluded that: (1) there is an influence between craft and entrepreneurship learning process with education’s facilities and infrastructure simultaneously toward entrepreneurial attitude, (2) there is an influence of craft and entrepreneurship learning process toward entrepreneurial attitude, and (3) there is no influence of education’s facilities and infrastructure toward entrepreneurial attitude.